1998
DOI: 10.1016/s0550-3213(98)00638-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon matrix elements of higher-twist operators from the instanton vacuum

Abstract: We compute the nucleon matrix elements of QCD operators of twist 3 and 4 in the instanton vacuum. We consider the operators determining 1/Q 2 -power corrections to the Bjorken, Ellis-Jaffe and Gross-Llewellyn-Smith sum rules. The nucleon is described as a soliton of the effective chiral theory derived from instantons in the 1/N c -expansion. QCD operators involving the gluon field are systematically represented by effective operators in the effective chiral theory. We find that twist-3 matrix elements are supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
80
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 29 publications
11
80
0
Order By: Relevance
“…We shall compute the matrix element (8) in the instanton model of the QCD vacuum using the technique of refs. [14,15]. The effective low-energy theory one derives from the instanton vacuum is formulated in terms of degrees of freedom which are pions (Goldstone bosons) and massive "constituent" quarks.…”
Section: The Mellin Moments Of H L (X) Can Be Splitted Into Twist-2 Amentioning
confidence: 99%
See 2 more Smart Citations
“…We shall compute the matrix element (8) in the instanton model of the QCD vacuum using the technique of refs. [14,15]. The effective low-energy theory one derives from the instanton vacuum is formulated in terms of degrees of freedom which are pions (Goldstone bosons) and massive "constituent" quarks.…”
Section: The Mellin Moments Of H L (X) Can Be Splitted Into Twist-2 Amentioning
confidence: 99%
“…[14] a method was developed to calculate hadronic matrix elements of mixed quark gluon operators in the instanton vacuum. Later this method was applied to estimates of higher twist operators [15]. In particular it was shown that the twist-3 contribution to the structure function g 2 is parametrically small relative to twist-2 and twist-4 contributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(6.5). One of possibilities to estimate these form factors is the theory of instanton vacuum [28,29]. However, one can easily see that the gluon operator (6.5) is exactly zero on the instanton field.…”
Section: Jhep01(2016)092mentioning
confidence: 99%
“…The interpretation of 2M 2 d 2 as an average transverse force also illustrates why d 2 is so small [27,[29][30][31]. Compared to the QCD string tension σ ≈ 1 GeV f m , the factor multiplying d 2 is rather large: 2M 2 ≈ 2GeV 2 ≈ 10σ .…”
Section: Transverse Force On Quarks In Dismentioning
confidence: 99%